Attention-Deficit/Hyperactivity Disorder Mimics the Post-concussion Syndrome in Adolescents - Cook, Nathan E.; Sapigao, Rosemarie G.; Silverberg, Noah D.; Maxwell, Bruce A.; Zafonte, Ross; Berkner, Paul D.; Iverson, Grant L. (Frontiers in Pediatrics, 2020)
The objective of this study was to evaluate concussion-like symptom reporting among uninjured adolescents with Attention-deficit/hyperactivity disorder (ADHD), stratified by several cooccurring conditions, and to examine the base rate and predictors of uninjured adolescents with ADHD meeting diagnostic criteria for the International Classification of Diseases, 10th Revision (ICD-10) post-concussional syndrome (PCS). Participants in this cross-sectional, observational study, were drawn from a cohort of 48,834 adolescent student athletes from Maine (ages 13–18) with no concussion in the past 6 months who completed a preseason, baseline testing program between 2009 and 2015. The final sample included 3,031 students with ADHD, 2,146 (70.8%) boys and 885 (29.2%) girls. They were 15.2 years old on average (SD = 1.3). Concussion-like symptom reporting was more common in girls than boys. Most students with ADHD reported one or more symptoms (69.3% of boys and 81.1% of girls). The presence of an additional, co-occurring condition or comorbidity was associated with increased symptom reporting. In the absence of a recent concussion, 28.8% percent of boys and 47.1% of girls with ADHD endorsed symptoms resembling an ICD-10 diagnosis of post-concussional syndrome (PCS). Adolescents with pre-existing conditions were even more likely to endorse symptoms that resembled PCS (28–47% of boys and 45–69% of girls). Prior treatment for a psychiatric condition was the strongest independent predictor for meeting PCS criteria in boys, followed by treatment for migraines and co-occurring learning disorder. For girls, the only independent predictor was prior treatment of a psychiatric condition. In uninjured adolescent student athletes, ADHD appears to mimic the post-concussion syndrome. Adolescents with ADHD commonly endorse concussion-like symptoms in the absence of a recent concussion. Demographic characteristics (sex) and the presence of co-occurring conditions are related to symptom reporting in adolescents with ADHD. Understanding factors associated with baseline symptom reporting, such as pre-existing ADHD, is important when evaluating youth who have persistent symptoms following concussion as well as making both return to school and return to athletics decisions.